A quantitative histochemical technique for the study of vascularization in tissue sections using horseradish peroxidase - Schwint, Amanda E.; Itoiz, María Elina; Cabrini, Rómulo Luis (Chapman and Hall Ltd., 1984)
Fil: Schwint, Amanda E. Comisión Nacional de Energía Atómica; Argentina